Association of age with 10-year outcomes after coronary surgery in the Arterial Revascularization Trial - Gaudino, M; Di Franco, A; Flather, M; Gerry, S; Bagiella, E; Gray, A; Pearcey, L; Saw, TH; Lees, B; Benedetto, U; Fremes, SE; Taggart, DP (Elsevier, 2021)
Background The association of age with the outcomes of bilateral internal thoracic arteries (BITAs) versus single internal thoracic arteries (SITAs) for coronary bypass grafting (CABG) remains to be determined.